Analysis of Islamic Religious Education Learning Outcomes Based on Students' School Origin - Murharyana, Murharyana; Al Ayyubi, Ibnu Imam; Rahmawati, Siti (Fahmina: Jurnal Pendidikan Islam, 2024)
This study aims to analyze learning outcomes in seeing the differences and interactions that occur between male and female students based on school origin in Islamic religious education learning. The research was carried out at MI Ar-Ridhwan, MIS Pasirpogor I, and MI Sukarasa. The method in this study uses the survey and test method of Analysis of Variance (ANOVA) with a sample of 33 students at MI Ar-Ridhwan, 20 students at MIS Pasirpogor I, and 24 students at MI Sukarasa with a total of 77 students in grade 4. This research instrument uses a test with testing the requirements of data analysis used consisting of normality tests using Kolmogorov-Smirnov and Shapiro-Wilk assisted by SPSS software version 26. In this study, it can be concluded that  the learning outcomes of PAI students reviewed based on school origin have significant differences, but there are no differences and interactions that occur when reviewed based on the gender of students, namely male and female students. The difference in learning outcomes occurred between MI Ar-Ridhwan and MIS Pasirpogor I and MI Sukarasa, but in MIS Pasirpogor I and MI Sukarasa there were no significant differences or tendencies in the same. Thus, for the next research, it is hoped that research can be carried out on the learning outcomes of PAI students which are reviewed based on the student's gender, weight, and height.